2016
DOI: 10.3844/ajeassp.2016.946.950
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Introduction to the Bird Strike Numerical Simulation

Abstract: Bird impacts can be extremely critical events for the air transport safety. Since aircraft structures have become more and more complex components, the numerical prediction of the damage onset and evolution induced by a bird impact has become a very challenging task. The aim of this work is to provide a brief overview of the numerical techniques adopted for the prediction of the bird impact phenomenon on a leading edge of a regional aircraft wing. Smooth Particle Hydrodynamics (SPH), Rigid and Lagrangian model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The Smoothed Particle Hydrodynamics (SPH) method is the most common and widely used in numerical simulations for any bird strike cases. Various approaches and other methods were presented and compared to be referred in a single study to differentiate the approaches to bird strike modelling [13].…”
Section: Bird Geometry and Sphmentioning
confidence: 99%
“…The Smoothed Particle Hydrodynamics (SPH) method is the most common and widely used in numerical simulations for any bird strike cases. Various approaches and other methods were presented and compared to be referred in a single study to differentiate the approaches to bird strike modelling [13].…”
Section: Bird Geometry and Sphmentioning
confidence: 99%
“…Unlike drone strike, bird strike has been studied extensively in the last decades and some of its information might be useful as a start point to explore damage due to drone strike with an aircraft engine. Bird strike is an airborne collision between flying birds and aircrafts, which is a major threat to flight safety in aviation as a bird strike can lead to serious structural damage [8][9][10]. According to the Federal Aviation Administration (FAA), it was reported that the bird strike accident had killed over 219 people and destroyed more than 200 aircrafts since 1988 [11].…”
Section: Introductionmentioning
confidence: 99%